Lack of sex- and gender-disaggregated data in diagnostics: findings from a scoping review of five tracer conditions - Upadhyay, Vishwanath; Gangwar, Rishabh; Chappuis, Gabrielle Landry; Kohli, Mikashmi (Frontiers in Public Health, 2025)
BackgroundSex and gender can affect all aspects of health-related behavior, yet there is limited information on how they influence diagnosis of any health condition. This scoping review examined the extent to which sex- and gender-disaggregated data on diagnostics are available for five tracer conditions: tuberculosis, coronavirus disease 2019 (COVID-19), diabetes, malaria, and schistosomiasis.MethodsPublications were searched between 2000 and 2022 on PubMed and Google Scholar and screened for relevance. Extracted data were analysed using descriptive quantitative and qualitative approaches.ResultsWe identified 29 relevant articles for tuberculosis, four for diabetes, six for schistosomiasis, eight for COVID-19, and three for malaria. For tuberculosis, most studies looked at gender-based barriers to diagnosis and disparities in health-seeking behaviors that predominantly affected women. For diabetes, studies noted that women had lower odds of being screened for prediabetes and potentially lower quality of care versus men. For schistosomiasis, studies suggested lower sensitivity diagnostic methods among women than men and low awareness of the disease. Studies suggest that women are less likely to be diagnosed for COVID-19 in certain settings. Studies on malaria reported that women show different health-seeking behaviors to men.ConclusionThis scoping review highlights a concerning lack of sex- and gender-disaggregated data on diagnostics. Consequently, further work is required to develop and implement an appropriate framework to assess gender and sex-related data around testing and diagnosis.